INTERNAL CONTROL IN THE INVESTMENT EXPENSES EXECUTION OF THE MUNICIPALITY OF INDEPENDENCE – ANCASH - Montes Espinoza, Yaneth Zenaida (2015)
The implementation of internal control in the District Municipality of Independence (DMI) in Ancash does not contribute to achieving its objectives and targets established in the expenses execution for investment projects; during the 2007 - 2011 period, the Entity did not complete the execution of investment projects scheduled in the Opening Institutional Budget (PIA) and the Institutional Operating Budget (POI), al-though it had available budget, generating complaints and discomfort in the population, in some cases in emerging areas. This study has shown that factors such as non-qualified personnel, failure of standards and policies, poor control of their resources- including the attitude of the entity ́s management - affected negati-vely on the implementation of control policies in the expenses execution of investment projects.